إدارة المعرفة وإشكالية تحسين أداء المنظمات في ظل الرهانات المعاصرة - رؤية مستقبلية- - فوزي, د/ عبد الرزاق; بلبال, أ/حسناوي (Sciences humaines; Vol. 42 (2015): SCIENCES HUMAINES (Novembre ), 2016)
يشهد الاقتصاد المعرفي في الآونة الأخيرة مجموعة من الرهانات والتحديات حول إمكانيته في مواجهة التطورات الحديثة، خاصة أنه أصبح في الوقت الحالي من الصعب على المنظمات تحقيق أهدافها والرفع من كفاءة أدائها بالطرق التقليدية، وإدارة المعرفة تشكل أساسا لبقاء المنظمات وتفوقها وتميزها لتأثيرها على تنافسيتها وأدائها.       وتهدف هذه الدراسة إلى تبيان مساهمة إدارة المعرفة من خلال توجهاتها الحديثة في تحسين أداء المنظمات خاصة في ظل التحولات الاقتصادية المعاصرة. الكلمات المفتاحية: المعرفة، إدارة المعرفة، الأداء، تحسين الأداء. Knowledge economy is faced in nowadays by many challenges about its ability to confront the recent developments, especially if we know that it has become very difficult in the present time for organizations to achieve their goals and increase the efficiency of their performance by traditional methods, and knowledge management, because of its impact on the competitiveness and performance of organizations, is one of the main basis for them to achieve superiority and excellence.       This study aims to demonstrate the contribution of knowledge management through its modern tendencies in improving the performance of organizations, especially with these contemporary economic transitions. Key words: knowledge, knowledge management, performance, improvement of performance.